The Impact of Experience, Motivation, and Technology on EFL Teachers' Creativity - Nathir Ghafar, Zanyar; Kale Burhan NEAMAT; Shno Waseem SIDIQ (RADINKA JAYA UTAMA PUBLISHER, 2025)
The primary responsibilities of teachers in the classroom are to enhance the motivation, experience, and technological proficiency of the teaching process and to teach learners in the modern era. Different variables, particularly EFL teachers' personal instructional experiences, often shape educators' opinions about effective teaching approaches, such as creativity or quality, and they contribute a range of skills to the learning environment. The objective of this study is to fully understand the procedures instructors take to remain current and the essential elements they require to maintain their creativity. The qualitative method was used, and 18 EFL instructors were interviewed to accurately collect the data and explore the elements that impact their creativity and their reasons for teaching creatively. The results identified three aspects that impacted instructors' creativity: their expertise and teaching background, their drive, and the impact of technology. The findings demonstrated that the three fundamentals guided instructors in incorporating creativity into their teaching methods. Additionally, English as a Foreign Language (EFL) instructors believed that their creativity was crucial in enhancing students' learning, promoting a pleasurable educational experience, and encouraging a sense of innovation among learners.